The “diagnose and leave in” strategy for diminutive rectosigmoid polyps in Lynch syndrome: a post hoc analysis from a randomized controlled trial - Rivero-Sánchez, Liseth; Gavric, Aleksandar; Herrero, Jesús; Remedios, David; Alvarez, Victoria; Albéniz, Eduardo; Gordillo, Jordi; Puig, Ignasi; López-Vicente, Jorge; Huerta, Alain; López-Cerón, María; Salces, Inmaculada; Peñas, Beatriz; Parejo, Sofía; Rodriguez, Enrique; Herraiz, Maite; Carretero, Cristina; Gimeno-Garcia, Antonio Z.; Saperas, Esteban; Alvarez, Cristina; Arnau-Collell, Coral; Ortiz, Oswaldo; Sánchez, Ariadna; Jung, Gerhard; Balaguer, Francesc; Pellisé, María (Endoscopy, 2021)
Background The “diagnose-and-leave-in” policy has been established to reduce the risks and costs related to unnecessary polypectomies in the average-risk population. In individuals with Lynch syndrome, owing to accelerated carcinogenesis, the general recommendation is to remove all polyps, irrespective of size, location, and appearance. We evaluated the feasibility and safety of the diagnose-and-leave-in strategy in individuals with Lynch syndrome.Methods We performed a post hoc analysis based on per-polyp data from a randomized, clinical trial conducted by 24 dedicated colonoscopists at 14 academic centers, in which 256 patients with confirmed Lynch syndrome underwent surveillance colonoscopy from July 2016 to January 2018. In vivo optical diagnosis with confidence level for all detected lesions was obtained before polypectomy using virtual chromoendoscopy alone or with dye-based chromoendoscopy. Primary outcome was the negative predictive value (NPV) for neoplasia of high-confidence optical diagnosis among diminutive (≤ 5 mm) rectosigmoid lesions. Histology was the reference standard.Results Of 147 rectosigmoid lesions, 128 were diminutive. In 103 of the 128 lesions (81 %), the optical diagnostic confidence was high and showed an NPV of 96.0 % (95 % confidence interval [CI] 88.9 %–98.6 %) and accuracy of 89.3 % (95 %CI 81.9 %–93.9 %). By following the diagnose-and-leave-in policy, we would have avoided 59 % (75/128) of polypectomies at the expense of two diminutive low grade dysplastic adenomas and one diminutive sessile serrated lesion that would have been left in situ.Conclusion In patients with Lynch syndrome, the diagnose-and-leave-in strategy for diminutive rectosigmoid polyps would be feasible and safe.